UPAYA MENGURANGI KANDUNGAN FOSFOR PO⁴ DI SUNGAI WANGGU KOTA KENDARI MENGGUNAKAN CONSTRUCTED WETLAND - Rachman, Ranno Marlany; Azizah, Siti Nur; Sriyani, Rini (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2023)
The high phosphorus (PO⁴) level in the Wanggu River is around 0.2459 mg/L. This value exceeds the Wanggu River water quality standard, which should be at 0.2 for class II based on Government Regulation No. 22 of 2021 regarding river water quality standards. Constructed wetlands are one way to deal with this. The purpose of this study is to determine the efficiency of reducing levels of phosphorus-type phosphorus (PO⁴) with the use and maintenance of Constructed Wetlands using a different method, namely water plants as the variable. The results showed that there was an 80% decrease in phosphorus (PO⁴) levels in water hyacinth (Eichornia crassipes) and a 98% decrease in water plants (Pistia stratiotes). This also happened to the water spinach plant (Ipomoea aquatica Forsk), which decreased by 86%. The most significant reduction percentage occurred in watercress (Pistia stratiotes), with the highest success rate, 98%.